2009
DOI: 10.1016/j.jaci.2009.07.036
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione-S-transferase Mu 1 null genotype modulates ozone-induced airway inflammation in human subjects

Abstract: Background-The Glutathione-S-Transferase Mu 1 null genotype has been reported to be a risk factor for acute respiratory disease associated with increases in ambient air ozone. Ozone is known to cause an immediate decrease in lung function and increased airway inflammation. However, it is not known if GSTM1 modulates these ozone responses in vivo in humans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 29 publications
0
46
1
Order By: Relevance
“…In addition to the epidemiological studies outlined in the introduction, GSTM1 null volunteers with asthma have increased nasal response to allergen after experimental diesel exhaust and tobacco smoke exposure,6 and we have shown that those with the GSTM1 null genotype have increased PMN influx to the airway 24 h following exposure to 0.4 ppm O 3. 9 In a cohort of volunteers who were exposed to 0.4 ppm O 3 and 20 000 EU CCRE on separate occasions, we found a strong within-individual correlation between O 3 and CCRE-evoked PMN response 12. Thus, susceptibility to O 3 also correlated with susceptibility to endotoxin (CCRE).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition to the epidemiological studies outlined in the introduction, GSTM1 null volunteers with asthma have increased nasal response to allergen after experimental diesel exhaust and tobacco smoke exposure,6 and we have shown that those with the GSTM1 null genotype have increased PMN influx to the airway 24 h following exposure to 0.4 ppm O 3. 9 In a cohort of volunteers who were exposed to 0.4 ppm O 3 and 20 000 EU CCRE on separate occasions, we found a strong within-individual correlation between O 3 and CCRE-evoked PMN response 12. Thus, susceptibility to O 3 also correlated with susceptibility to endotoxin (CCRE).…”
Section: Discussionmentioning
confidence: 70%
“…All volunteers had normal lung function, normal methacholine challenge and negative skin tests and were genotyped only after challenge and assessment of samples was completed, thus avoiding selection bias. Venipuncture, induced sputum, spirometry, cytokine measurements in sputum and genotyping for GSTM1 were performed as previously described 8 9. Circulating total WBCs, PMNs and platelet counts, sputum PMNs and mediators in recovered sputum samples, spirometry measures and symptom scores were assessed at baseline (pre-challenge) and 4 h after CCRE challenge was complete in GSTM1 null and sufficient cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with the GSTMI null genotype have increased neutrophil influx to the airway 24 hours following exposure to ozone at a level of 400 ppb [51]. A study by Wu et.…”
Section: Oxidative Stress Genes and Susceptibility To Air Pollutionmentioning
confidence: 99%
“…Subjects inhaled LPS via a DeVilbiss Ultraneb 99 ultrasonic nebulizer. Induced sputum was obtained 4 hours post-LPS inhalation and processed as previously described (20-23). Cell viability (trypan blue exclusion) and total cell counts were assessed in a Neubauer hemacytometer and differential cell counts were performed on cytocentrifuged cells stained with a modified Wright's stain, (Hema-Stain -3, Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%